Association between consumption of edible seaweeds and newly diagnosed non‐alcohol fatty liver disease: The TCLSIH Cohort Study. (19th January 2021) - Li, Huiping; Gu, Yeqing; Wu, Xiaohui; Rayamajhi, Sabina; Bian, Shanshan; Zhang, Qing; Meng, Ge; Liu, Li; Wu, Hongmei; Zhang, Shunming; Wang, Yawen; Zhang, Tingjing; et al.
Abstract: Background & aims: Seaweeds are rich sources of anti‐oxidants and anti‐inflammatory properties, which are beneficial to non‐alcoholic fatty liver disease (NAFLD). However, whether seaweed consumption is associated with NAFLD is unknown. We investigated the association of seaweed consumption with newly diagnosed NAFLD in a large‐scale adult population. Methods: This cross‐sectional study involved 24 572 participants aged over 18 years. NAFLD was diagnosed by results of liver ultrasonography and alcohol intake. Dietary information was assessed using a validated and standardized 100‐item food frequency questionnaire. Multivariate logistic analysis was used to evaluate the association between seaweed consumption and NAFLD. Results: The prevalence of newly diagnosed NAFLD was 20.1%. After adjustment for sociodemographic characteristics, lifestyle factors, and other dietary intakes, the multivariable adjusted odds ratios (95% confidence intervals) of newly diagnosed NAFLD across seaweed consumption were 1.00 (reference) for almost never, 1.03 (0.93, 1.15) for <1 time/wk, 1.01 (0.90, 1.13) for 1 time/wk, and 0.84 (0.73, 0.96) for >1 times/wk ( P for trend < .001). Stratified analyses suggested a potential effect modification by obesity status; the odds ratios (95% confidence intervals) across extreme quartiles was 0.77 (0.66, 0.91) in non‐obese participants and 1.02 (0.79, 1.33) in obese participants ( P for interaction < .001). Conclusion: Seaweed consumption is negatively associated with NAFLD, especially in non‐obese participants.